2023
DOI: 10.1021/acsomega.2c08124
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Characterization of Solanum nigrum and Mentha arvensis Leaf Extracts Using Caenorhabditis elegans as a Model Organism

Abstract: Considering foremost global issues instigated by parasitic nematodes, Solanum nigrum (S. nigrum) and Mentha arvensis (M. arvensis) nematicidal potential at the gene level has been explored herein. Methanol, ethyl acetate, chloroform, n-hexane, and distilled water were used for extract preparation. Caenorhabditis elegans (C. elegans) was used as the model organism. Nematicidal and anti-egg hatching assays, fluorescence microscopy, and quantitative real-time PCR were done. S. nigrum chloroform (LD 50 = 1.21 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Khan et al also screened out the expression of stress genes in transgenic C. elegans affected by plant extracts and then confirmed through quantitative qRT-PCR .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al also screened out the expression of stress genes in transgenic C. elegans affected by plant extracts and then confirmed through quantitative qRT-PCR .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Khan et al 39 also screened out the expression of stress genes in transgenic C. elegans affected by plant extracts and then confirmed through quantitative qRT-PCR. 39 In the reference of the above study, it was confirmed that compounds 4, 5, 7, 12, 13, 14, and 15 are the most potent compounds and expressed more genes as shown in Figure 6 . This technique shows that thiazine derivatives expressed stress response genes (genes involved in stress).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The same study also showed that menthol can significantly potentiate the contraction of Ascaris suum somatic muscle strips at each concentration of acetylcholine. A study by Khan et al (69) showed that methanol and the extract of M. arvensis cause high apoptotic effect in the muscles, gonads, and uterus (eggs) of the freeliving nematode Caenorhabditis elegans, which was used as a model organism. The results also showed that stress genes (gst-4 and hsp-16.2) were highly expressed in the affected nematodes compared to normal C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by El-Tekreti et al [99] reported the nematicidal activity of NCs based on Al 2 O 3 -NPs, SiO 2 -NPs and ZnO-NPs against root-knot nematodes on cucumber plants by inhibiting egg hatching and reducing the number of second instars. Chitosan-silver doped titanium dioxide NCs (Cs-AgTiO 2 ) showed excellent nematicidal potential against Caenorhabditis elegans [100]. Tryfon et al [101] demonstrated Cu-doped ZnO NPs as a promising tool to control M. javanica on lettuce plants by reducing galling and population and increasing antioxidant capacity and phenolic compounds.…”
Section: Nanocomposites and Their Mode Of Action Against Phytopathoge...mentioning
confidence: 99%